Modeling and Retrieval of Context c - Roth-Berghofer, Thomas R.; Schulz, Stefan; Leake, David B.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
Computing in context has become a necessity in modern and intelligent IT - plications. With the use of mobile devices and current research on ubiquitous computing, context-awareness has become a major issue. However, context and context-awareness are crucial not only for mobile and ubiquitous computing. They are also vital for spanning various application areas, such as collaborative softwareand Web engineering,personaldigital assistantsand peer-to-peer inf- mation sharing, health care work?ow and patient control, and adaptive games and e-learning solutions. In these areas, context serves as a major source for reasoning, decision making, and adaptation, as it covers not only application knowledge but also environmental knowledge.Likewise, modeling and retrieving context is an important part of modern knowledge management processes. In addition, context can play a role in determining what information a s- tem should provide. This is important for supporting the users of automated or intelligent systems, for tasks such as explaining how solutions are found, what the system is doing, and why it operates in a certain way. The methods applied and the advice given have to be explained, so that the user can understand the process and agree on decisions. Context is equally important for deciding when to provide uncertain or blurred information, e.g., when using a tracking system in situations for which either revealing the current position, or denying access to it, would have adverse e?ects. In this wide range of applications, context is now more than just location.
Using Activity Theory to Model Context Awareness -- A Context Model for Personal Knowledge Management Applications -- Situation Modeling and Smart Context Retrieval with Semantic Web Technology and Conflict Resolution -- An Architecture for Developing Context-Aware Systems -- Steps Towards Making Contextualized Decisions: How to Do What You Can, with What You Have, Where You Are -- A Layered Model for User Context Management with Controlled Aging and Imperfection Handling -- Designing the Context Matching Engine for Evaluating and Selecting Context Information Sources -- Identifying the Multiple Contexts of a Situation -- An Engineering Approach to Adaptation and Calibration.
Keywords: Mathematics; Mathematical logic; Artificial intelligence; Application software; System theory; Mathematics; Systems Theory, Control; Artificial Intelligence (incl. Robotics).; Mathematical Logic and Formal Languages; Computer Appl. in Social and Behavioral Sciences; Computer Appl. in Arts and Humanities; Electronic books